2013
DOI: 10.1063/1.4796137
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic transient electrical currents and phonon heating in a single-level quantum dot system

Abstract: We present a theoretical study on inelastic transient electrical currents and the effects of phonon heating in a single-level quantum dot system weakly coupled to a localized vibration degree of freedom, using the nonequilibrium Green's function method under the wide-band-limit and the lowest-order-expansion approximations. The energy transfer between electron and phonon systems is evaluated using both approximations, which separately are exact in the limits of the equilibrium state (t < 0) and steady s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…For this model, we simulate the TD current using the NEGF technique under the wide band limit approximation, 6,7,10,[13][14][15]17,18) in which the level broadening due to ¡ electrode, À ; , is independent of energy ( ¼ L, R). In this technique, the spin component of the TD current from the QD into ¡ electrode is expressed as…”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this model, we simulate the TD current using the NEGF technique under the wide band limit approximation, 6,7,10,[13][14][15]17,18) in which the level broadening due to ¡ electrode, À ; , is independent of energy ( ¼ L, R). In this technique, the spin component of the TD current from the QD into ¡ electrode is expressed as…”
Section: Model and Methodsmentioning
confidence: 99%
“…Actually, nanosecond dynamics has been experimentally observed in a quantum capacitor, 1) a quantum point contact, [2][3][4] and a single-atom contact. 5) On the other hand, the simulation methods for time-dependent quantum transport have been developed, such as the non-equilibrium Green's function (NEGF) method, [6][7][8][9][10][11][12][13][14][15][16][17][18] Liouville equation, [19][20][21] and time-dependent density functional theory (TD-DFT). [22][23][24] Many of computational works have shown that the temporal oscillations of electrical current appear right after the sudden switching-on of voltage in a variety of nano-scale systems.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, also the partitioning protocols between the dot and the leads have been investigated [327] disentangling dynamical charge rearrangements due to the dot-lead contacting. Phonons or vibrons may also induce or mediate dynamical effects, such as spin-flip processes [478], heating [479,480] or electron correlations [481].…”
Section: Electronic Transportmentioning
confidence: 99%
“…In this context, also the partitioning protocols between the dot and the leads have been investigated [280] disentangling dynamical charge rearrangements due to the dot-lead contacting. Phonons or vibrons may also induce or mediate dynamical effects, such as spin-flip processes [434], heating [435,436] or electron correlations [437] Modeling the electron-phonon coupling can also be extended to larger systems. Nuclear dynamics in a quantum transport setup of atomic-ring structures were investigated in Ref.…”
Section: Electronic Transportmentioning
confidence: 99%